An Introductory Study On Fabrication Of Piezoelectric Ceramic - Bachok, Zuraihana (Universiti Sains Malaysia, 2004)
This thesis gives a quite detailed overview of piezoelectric ceramics. It will be beneficial to general reader to get basic ideas about this smart material once the reader going through this thesis. The scope of this work is limited to the development of ceramic piezoelectric, related to the scope of work which the objectives of the study are to focus on its manufacture of the green material, the poling process and the study of its physical and electrical characteristics. Processing of Barium Titanate (BaTiO3) ceramic by mixed oxide method for high technology applications involves the sequential steps; (a) powder preparation (b) powder calcining (c) de-agglomeration (d) forming (e) sintering (f) electroding (g) and poling. Each step is critical to the realization of desirable structure property relationships.